Pertussis Seroprevalence in Korean Adolescents and Adults Using Anti-Pertussis Toxin Immunoglobulin G - Lee, Soo Young (The Korean Academy of Medical Sciences, 2014)
This study was conducted to evaluate age-specific seroprevalence of pertussis in Korea and to formulate a strategy to prevent and reduce the incidence of pertussis. Residual serum samples of healthy adolescents and adults 11 yr of age or older were collected between July 2012 and December 2012, and anti-pertussis toxin (PT) IgG titers were measured using a commercial ELISA kit. We compared the mean anti-PT IgG titers and seroprevalence of pertussis of the six age groups: 11-20, 21-30, 31-40, 41-50, 51-60, and ≥ 61 yr. A total of 1,192 subjects were enrolled. The mean anti-PT IgG titer and pertussis seroprevalence were 35.53 ± 62.91 EU/mL and 41.4%, respectively. The mean anti-PT IgG titers and seroprevalence were not significantly different between the age groups. However, the seroprevalence in individuals 51 yr of age or older was significantly higher than in individuals younger than 51 yr (46.5% vs 39.1%, P = 0.017). Based on these results, a new pertussis prevention strategy is necessary for older adults. GRAPHICAL ABSTRACT: [Image: see text]